(untitled) - World Trade Organization (Cambridge, UK, 2004)
Published by the Secretariat of the World Trade Organization, this is a training guide intended to aid public understanding of the WTO dispute settlement system. It describes the historic development of the system and explains the roles of the various WTO bodies involved in the system. It then discusses the legal and jurisdictional basis for a dispute. The stages of a typical case are described and the legal effects of case results are explored. An annex provides reproductions of relevant legal texts.
Keywords: World Trade Organization,Foreign trade regulation,Tariff,Arbitration and award, international,Dispute resolution ( law ); Rrules and practice,Law and legislation